2014
DOI: 10.1017/s002185961400029x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat seedlings growth response to water deficiency and how it correlates with adult plant tolerance to drought

Abstract: Improving resistance to water and osmotic stresses at the seedling stage is becoming a much more important target for wheat breeders due to an increase in the frequency and severity of drought occurrences at the crop establishment and tillering phases in many wheat growing areas of the world. Ninety-six diverse wheat genotypes were laboratory tested for germination and growth response under osmotic stress induced by polyethylene glycol (PEG). Germination percentage, mean germination time, coleoptile length, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…This confirmed the work on sugar beet of Sadeghian and Yavari [25] who reported that seedling growth severely diminished under drought stress however genetic differences were monitored among the varieties. Moreover, Dodig et al [26] showed on their works on wheat that, the effect of drought stress was most informative for differentiating between the genotypes for the studied seedling traits. In water stress in all phases (W5), reduction in performance of seeds was more intense for SE ( Table 2); similar to the results obtained for the variables seedling fresh weight (SFW) and seedling dry weight (SDW).…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed the work on sugar beet of Sadeghian and Yavari [25] who reported that seedling growth severely diminished under drought stress however genetic differences were monitored among the varieties. Moreover, Dodig et al [26] showed on their works on wheat that, the effect of drought stress was most informative for differentiating between the genotypes for the studied seedling traits. In water stress in all phases (W5), reduction in performance of seeds was more intense for SE ( Table 2); similar to the results obtained for the variables seedling fresh weight (SFW) and seedling dry weight (SDW).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies in other crop species (e.g. Beshir et al, 2016;Dodig et al, 2015), including in cowpea (Singh et al, 1999), have revealed a close correspondence of drought tolerance observed in seedlings and reproductive stage plants. Different seed germination and seedling emergence capacities were displayed by distinct cowpea genotypes under stress conditions.…”
Section: Tablementioning
confidence: 92%
“…Drought conditions at early growth stages are known to reduce seed germination percentage and rate and it can affect negatively seedling establishment. The developing plants will have poor tillering capacity leading to fewer plants and tillers per unit area and thus lower yield potential [7]. Additionally, drought at the period of stem elongation causes reduction in number of grains per unit area due to it is negative effect on floret formation and fertility [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The developing plants will have poor tillering capacity leading to fewer plants and tillers per unit area and thus lower yield potential [7]. Additionally, drought at the period of stem elongation causes reduction in number of grains per unit area due to it is negative effect on floret formation and fertility [7,8]. Post-anthesis drought conditions reduce the grain filling rate and duration and this will result in shriveled grains [9].…”
Section: Introductionmentioning
confidence: 99%